356 Reducing Long Term Opioid Prescribing Post Thoracic Surgery. (4th May 2021) - Allen, N; Gregg, A; McGuigan, J
Abstract: Introduction: Patients are routinely started on strong opioid analgesia after surgery with most receiving a prescription for these to continue discharge. We examine the analgesia prescribed in our unit, comparing to ERAS principles from EACTS. We aimed to reduce the total equivalent dose of morphine prescribed on discharge by implementing ERAS principles. Method: We undertook a retrospective analysis of the analgesia prescribing for patients post open and VATS procedure noting the total dose opioids (using the equivalent dose of morphine). We examined how many patients were still being prescribed opioids analgesia long term, defined as 6 weeks post procedure. We implemented ERAS principles, changing to morphine rather than oxycodone, using short-acting preparations and increasing use of opioid sparing analgesia including NSAIDs. Results: 20% of patients started on strong opioids post procedure were still being prescribed these 6 weeks later. We used ERAS principles to reduce the equivalent dose of morphine dispensed on discharge by a third. Conclusions: We identified a significant issue with long term opioid prescribing and initiated measures which have resulted in positive change. Our next cycle will measure the outcome of our changes on long-term prescribing implement a multi-disciplinary approach to try reducing the burden of long-term opioid prescribing further.